Factors Affecting the Behavioral Intention to Use Mobile Fintech Payment Channel in Bangkok - Meepien, Premyuda; Chaivisuttangkun, Sirithida (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2023)
The study examines the intention to use mobile banking in Bangkok and the factors influencing this behavior. We analyze the behavioral intention across different age groups and education levels. The results indicate that perceived ease of use, perceived usefulness, attitude, perceived behavioral control, perceived security, and intention behavior significantly impact the willingness to use mobile banking. However, subjective norm and perceived COVID-19 risk were found to be insignificant factors in this context.